Landscape design as part of green and sustainable building design - Mohd. Hussain, Mohd. Ramzi; Nizarudin, Norhanis Diyana; Tukiman, Izawati (Trans Tech Publications, Switzerland, 2014)
This paper presents the theoretical review of the importance of landscape design in the execution of green and sustainable buildings as a trend of current development concept. Instead of beautifying the environment, strategic landscape design may help to prevent from extensive building heat gain, reduce the energy and water consumption as well as produce the natural and healthy ambience to the surrounding. Landscape design in green buildings should be viewed as not just mere decorative afterthought but it must be well conceived as a multi-function factor that provides various critical green services for a building including water efficiency and energy efficiency. The framework covers two main aspects which are green wall or vertical landscape design and roof top garden. The aim of the paper is to highlight the demand for the proper landscape design that should be provided in any development of sustainable buildings. It is hoped that the paper will contribute to further enrich the landscape design innovation as part of green and sustainable building design.